2015
DOI: 10.1088/1748-0221/10/12/p12017
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction method for grating-based x-ray phase-contrast images without knowledge of the grating positions

Abstract: To retrieve the phase information of x-rays using a Talbot-Lau interferometer, the knowledge of the grating positions is mandatory. Transferring the interferometer technique from the laboratory to a conventional x-ray imaging system, this requirement is no longer guaranteed. This is due to distortions and vibrations which are coupled into the interferometer. Therefore, we applied a principal-component analysis to Talbot-Lau x-ray phase-contrast data. In experiments we compared this alternative approach for ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Using principle component analysis (PCA), all step positions can be retrieved in a single, fast computation step. It has been adapted for gbPC imaging by Pelzer et al [26], but does not perform well for low numbers of moiré fringes and strongly attenuating samples. A combination of this method with the one given in [23] was presented in [27], which combines the applicability of PCA for arbitrary step positions with the high quality of results achieved with the method from [23].…”
Section: Discussionmentioning
confidence: 99%
“…Using principle component analysis (PCA), all step positions can be retrieved in a single, fast computation step. It has been adapted for gbPC imaging by Pelzer et al [26], but does not perform well for low numbers of moiré fringes and strongly attenuating samples. A combination of this method with the one given in [23] was presented in [27], which combines the applicability of PCA for arbitrary step positions with the high quality of results achieved with the method from [23].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we want to point out that the presented full‐body scan of the pig demonstrates that the phase‐stepping method is feasible for dark‐field imaging of human‐sized objects under clinical conditions. In addition, the system's acquisition speed and robustness toward external influences could be even further increased by implementing single‐shot dark‐field imaging techniques, using motionless phase‐stepping, or refining the image reconstruction …”
Section: Discussionmentioning
confidence: 99%
“…The noise properties of this algorithm were later investigated by Weber et al 24 Yang et al 25 developed a phase-stepping reconstruction method for nonideal gratings, which may exhibit a phase-stepping curve with twin peaks. The problem of estimating the position of misaligned phase steps was considered by Pelzer et al 26 and Seifert et al 27 They showed that an algorithm known in optics 28 can be used to retrieve the correct phase-stepping positions, if the Talbot-Lau interferometer is detuned by rotation of either G1 or G2, such that sufficient moiré fringes appear in the reference phase, and if a sufficient number of phase steps are available. However, detuning the interferometer reduces visibility.…”
Section: Prior Workmentioning
confidence: 99%